2017
DOI: 10.1136/bmjgh-2017-000452
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a bovine colostrum and egg-based intervention in acute childhood diarrhoea in Guatemala: a randomised, double-blind, placebo-controlled trial

Abstract: BackgroundTreatments for paediatric diarrhoeal disease are limited. We assessed the impact of a bovine colostrum and egg-based treatment designed to reduce diarrhoea duration through non-specific and pathogen-directed mechanisms in children.MethodsRandomised, double-blind, placebo-controlled trial of PTM202, derived from bovine colostrum and hyperimmune hen’s egg on the duration of acute diarrhoeal disease in Guatemalan children. PTM202 contains specific immunoglobulins that target rotavirus, enterotoxigenic E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These trials suggest that colostrum has clinical value for NSAID-induced gut injury [9], chemotherapy induced mucositis [17] and inflammatory bowel disease [18]. In addition, colostrum may have value for reducing symptoms of infective diarrhea [19], possibly acting through its specific (antibodies) and general antimicrobial constituents such as lactoferrin. Colostrum may also have value as a sports nutritional supplement to reduce the incidence of upper respiratory tract infections during training [15] and to reduce the increased gut permeability that occurs during heavy exercise [20].…”
Section: Discussionmentioning
confidence: 99%
“…These trials suggest that colostrum has clinical value for NSAID-induced gut injury [9], chemotherapy induced mucositis [17] and inflammatory bowel disease [18]. In addition, colostrum may have value for reducing symptoms of infective diarrhea [19], possibly acting through its specific (antibodies) and general antimicrobial constituents such as lactoferrin. Colostrum may also have value as a sports nutritional supplement to reduce the incidence of upper respiratory tract infections during training [15] and to reduce the increased gut permeability that occurs during heavy exercise [20].…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria tested in the current series of experiments covered the most common aerobic organisms cultured from patients with SIBO. In addition, we included two more toxic bacteria associated with episodic diarrhea, i.e., EPEC and Salmonella , to determine if common protective mechanisms were present across bacteria with differing toxicity and because a BC and egg combination had been reported to reduce diarrhea caused by these organisms [ 18 ]. The addition of BC, egg, or the combination did not inhibit growth of the bacteria in vitro, which were results in keeping with previous findings that hyperimmune IgY antibodies raised against 078:K80 E coli .…”
Section: Discussionmentioning
confidence: 99%
“…We had previously shown that 1 mg/mL was the optimal concentration for BC or egg for inducing proliferation and migration in a variety of gut cell lines including Caco-2 cells, without causing any toxic effects [ 17 ]. Similarly, the 60:40 BC/egg ratio was used as it had been shown to reduce duration of diarrhea in patients with infectious diarrhea [ 18 ] and we previously showed synergistic responses when used in this ratio for reducing DSS-induced colitis and NSAID-induced small intestinal injury [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized, double-blind, placebo-controlled trial evaluated 301 Guatemalan children (154 intervention and 147 placebo) with acute non-bloody diarrhea who received PTM202 (combined IgY specifically targets rotavirus, enterotoxigenic E. coli , Shiga toxin-positive E. coli , and salmonella) or placebo for 3 days ( 237 ). PTM202 led to a reduction in duration of diarrhea among children whose diarrheal stool at enrollment contained one or more PTM202-targeted organisms.…”
Section: Treatment Of Bacterial Infectionsmentioning
confidence: 99%